PGD2/PTGDR2 signaling pathway affects the self-renewal capacity of gastric cancer stem cells by regulating ATG4B ubiquitination - Zhang, Qiang; Tian, HengJin; Ge, Kunpeng; Wang, FeiFan; Gao, PeiYao; Chen, AMin; Wang, Lulu; Zhao, YanMing; Lian, Chaoqun; Wang, FengChao (Frontiers in Oncology, 2024)
BackgroundProstaglandin D2 (PGD2) inhibits the development of different malignant tumors; however, the underlying mechanism of inhibiting tumor development is not yet clear. This study aimed to elucidate how PGD2 inhibits the stemness of gastric cancer stem cells (GCSCs) via autophagy and its underlying molecular mechanism to provide a theoretical basis for the treatment of gastric cancer.MethodsIn this study, GCSCs were enriched in vitro by serum-free incubation. Furthermore, the effects of PGD2 and PGD2 receptor (PTGDR2) on autophagy were detected by Western blotting, immunofluorescence analysis, and transmission electron microscopy. Moreover, the ATG4B ubiquitination levels were assessed via immunoprecipitation and other methods.ResultsThe results indicated that PGD2 induced LC3I/LC3II conversion in GCSCs to activate autophagy, while PGD2 promoted the expression of PTGDR2, thereby further activating autophagy. Furthermore, PTGDR2 competes with ATG4B for binding with E3 ligase RNF5 (also known as RMA1) to promote autophagy protein ATG4B expression. Moreover, PTGDR2 knockdown blocked the activation of autophagy by PGD2 and the level of ATG4B ubiquitination in GCSCs.ConclusionsIn summary, it was elucidated that the PGD2/PTGDR2 signaling cascade affects GCSCs stemness by regulating autophagy, suggesting that the PGD2/PTGDR2 signaling pathway could serve as a novel target for cancer therapy.